Perancangan Arsitektur Enterprise Menggunakan Metodologi Enterprise Architecture Planning (EAP): (Studi Kasus PT. Surya Logam Indoabadi Ciputat Tanggerang) - Adisuputra Adisuputra; Ditra Liandaputra (Politeknik Kampar, 2024)
Enterprise Architecture Planning (EAP) is a framework for architectural planning that encompasses data architecture, application architecture, and technology architecture, with business processes as its foundation. PT Surya Logam Indoabadi, a manufacturing company specializing in metal-based products, faces challenges in system integration due to conventional business processes. The lack of data synchronization across divisions hampers operational efficiency, particularly in raw material management, production scheduling, and distribution. Without adequate information technology utilization, the company risks operational delays and difficulties in competing within the manufacturing industry. Fragmented systems create